The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1039/c8ra06884d
|View full text |Cite
|
Sign up to set email alerts
|

The activity and stability of CeO2@CaO catalysts for the production of biodiesel

Abstract: The stability test results for the CaO, CeO2@CaO-60 and CeO2–CaO-60 catalysts for biodiesel production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…31 Another weak peak of oxygen at 529.8 eV typically indicates the bonding of oxygen with Ca. 32 The binding energies of P 2p 3/2 and P 2p 1/2 are located at 133.0 and 134.0 eV, respectively, 33 as depicted in Fig. 4c .…”
Section: Resultsmentioning
confidence: 94%
“…31 Another weak peak of oxygen at 529.8 eV typically indicates the bonding of oxygen with Ca. 32 The binding energies of P 2p 3/2 and P 2p 1/2 are located at 133.0 and 134.0 eV, respectively, 33 as depicted in Fig. 4c .…”
Section: Resultsmentioning
confidence: 94%
“…Then, sodium loading is necessary to generate active sites that carry out the transesterification reaction [27]. As seen in CO2-TPD patterns and XPS, sodium promotes the generation of medium and strong basic sites on the catalyst surface and essential for the reaction to take place [48]. As Ambat et al reported, methanol is adsorbed on Lewis and Brønsted basic sites of the solid catalyst J o u r n a l P r e -p r o o f…”
Section: Catalytic Activitymentioning
confidence: 99%
“…Elías et al reported the "shielding effect" that a second metal could produce over the first one while coating the catalyst surface with a layer of a metallic oxide, which might prevent leaching of active species during the reaction [29]. In this way, CeO2 could have a shielding effect on Na species [48]. Furthermore, as reported by Thitsartarn et al, there could also be an interaction between Na and Ce due to some vacancies created by the substitution of Ce ions by Na ions in the ceria phase during calcination.…”
Section: Catalyst Reusabilitymentioning
confidence: 99%
“…The CeO2 magnetic nanoparticles were impregnated with various concentration of potassium ions to determine the doping effect of potassium ions on catalytic activity. The cerium oxide was used in combination with various metal oxides for transesterification reaction [37,38]. Moreover, ceria was used as catalyst for various catalytic reactions [15,39].…”
Section: Introductionmentioning
confidence: 99%